2017 IEEE International Conference on Image Processing (ICIP) 2017
DOI: 10.1109/icip.2017.8297018
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-parameter optimization for convolutional neural network committees based on evolutionary algorithms

Abstract: In a broad range of computer vision tasks, convolutional neural networks (CNNs) are one of the most prominent techniques due to their outstanding performance. Yet it is not trivial to find the best performing network structure for a specific application because it is often unclear how the network structure relates to the network accuracy. We propose an evolutionary algorithm-based framework to automatically optimize the CNN structure by means of hyper-parameters. Further, we extend our framework towards a join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 10 publications
0
68
0
3
Order By: Relevance
“…Baldominos et al [63] presented a work in 2018 where the topology of the network is evolved using grammatical evolution, attaining a test error rate of 0.37% without data augmentation and this result was later improved by means of the neuroevolution of committees of CNNs [64] down to 0.28%. Similar approaches of evolving a committee of CNNs were presented by Bochinski et al [65], achieving a very competitive test error rate of 0.24%; and by Baldominos et al [66], where the models comprising the committee were evolved using a genetic algorithm, reporting a test error rate of 0.25%.…”
Section: State Of the Artmentioning
confidence: 87%
See 1 more Smart Citation
“…Baldominos et al [63] presented a work in 2018 where the topology of the network is evolved using grammatical evolution, attaining a test error rate of 0.37% without data augmentation and this result was later improved by means of the neuroevolution of committees of CNNs [64] down to 0.28%. Similar approaches of evolving a committee of CNNs were presented by Bochinski et al [65], achieving a very competitive test error rate of 0.24%; and by Baldominos et al [66], where the models comprising the committee were evolved using a genetic algorithm, reporting a test error rate of 0.25%.…”
Section: State Of the Artmentioning
confidence: 87%
“…Batch-normalized maxout network-in-network [29] 0.24% Committees of evolved CNNs (CEA-CNN) [65] 0.24% Genetically evolved committee of CNNs [66] 0.25% Committees of 7 neuroevolved CNNs [64] 0.28% CNN with gated pooling function [30] 0.29% Inception-Recurrent CNN + LSUV + EVE [60] 0.29% Recurrent CNN [31] 0.31% CNN with norm. layers and piecewise linear activation units [32] 0.31% CNN (5 conv, 3 dense) with full training [45] 0.32% Table 2.…”
Section: Technique Test Error Ratementioning
confidence: 99%
“…A limitation to this approach is that it can only be used on new models trained from scratch. In contrast to post-processing techniques, architecture generation algorithms such as [33][34][35][36][37] have demonstrated that architectures can be automatically generated by exploring different architecture choices and hyper-parameter settings. Ref.…”
Section: Related Workmentioning
confidence: 99%
“…In the works proposed by Suganuma et al [26] and by Davison [27], genetic programming is used instead for evolving the architecture of the CNN. Meanwhile, Bochinski et al [28] proposed IEA-CNN, an approach using an evolutionary strategy, innovating by sorting the evolved layers by descending complexity, effectively reducing the search space factorially on the number of layers. Additionally, they extend their contribution by building ensembles out of evolved models, using a fitness function that takes the global classification error of the population, and naming this alternative CEA-CNN.…”
Section: Complexitymentioning
confidence: 99%
“…In recent years, this idea has been applied to a variety of fields, such as facial expression analysis [36], astrophysics [37], pose estimation [38], or medical imaging [39]. However, the idea of building an ensemble out of a population of neuroevolved CNN topologies is less common and, to the best of our knowledge, has been only explored before by Real et al [23] and by Bochinski et al [28] in 2017. In the former work, the ensemble is built by choosing the top-2 models of the evolved population based on validation accuracy.…”
Section: Complexitymentioning
confidence: 99%